The Role of Sport Leadership and Woman’s Position - Grigoriou Στεφανία Σ.; Grigoriou Ιωάννα; Aspridis Γιώργος (Inquiries in Physical Education and Sport, 2012)
The fact is, leaders are able to see better and farther than anyone, so we shape events instead of shaping them. Specifically in sport, one leader can convince a group of people to leave aside their individual pursuits and pursue a common goal and that is important for the welfare of the group. This review of contemporary literature aims to brief study and recording of the main features that should be included in the profile of a capable leader and to highlight the importance of its role in the modern period. Also an ultimate goal of this study is to place and position of women in the realm of leadership and demonstrated any benefits may be the accessibility of it. The findings are particularly important and any recovery will help to improve athletic leadership in a global society.